Nursing ethical dimensions of euthanasia and medically assisted suicide for older people in need of long-term care - Anna-Henrikje Seidlein; Annette Riedel; Thomas Heidenreich; Karen Klotz (Frontiers in Psychiatry)
Euthanasia and medically assisted suicide (E/MAS) are (healthcare-)practices intended to cause a patient’s death according to their wish and will. This article addresses the specific ethical questions that arise in the context of E/MAS regarding older adults in need of long-term care (LTC) from a nursing ethics perspective. Older people in need of LTC are particularly vulnerable due to a combination of health-related, social, and economic factors. Multiple chronic diseases, age-related frailty and the subsequent need for LTC, for example, may contribute to an increased risk of social isolation, loneliness and hopelessness. The boundaries between “normal” age-related changes and changes that are deemed to be pathological also become blurred. The complex interplay of these factors results in the particular needs of older adults who rely on nursing care. Consequently, specific ethical issues arise that are unique in terms of their quality and quantity – also regarding E/MAS. We present a common scenario: a fall with a subsequent fracture, as a turning point in the LTC arrangement. The consequences of such an adverse event (limited mobility, risk of further falls) compromise the security of care at home, raising the (potential) need for transfer to a LTC facility. This (potential) move represents a major disruption, is experienced as a crisis, and marks a transition for the older adult in need of LTC. We highlight the complex interplay between aging, health-care dependency, personal values and the resulting wish/request for E/MAS. We discuss how the professional self-perception and ethical values of the nursing profession in the home care setting determine the treatment pathway for older peoples’ request for E/MAS.